ArsM-mediated arsenite volatilization is limited by efflux catalyzed by As efflux transporters. (January 2020) - Yang, Pengmin; Ke, Changdong; Zhao, Chungui; kuang, Qingyue; Liu, Bixiu; Xue, Ximei; Rensing, Christopher; Yang, Suping
Abstract: Arsenic (As) methylation is regarded as an efficient strategy for As contamination remediation by As volatilization. However, most microorganisms display low As volatilization efficiency, which is possibly linked to As efflux transporters competing for cytoplasmic As(III) as a substrate. Here, we developed two types of As biosensors in Escherichia coli to compare the As efflux rate of three efflux transporters and to further investigate the correlation between As efflux rates and As volatilization. The engineered As-sensitive E. coli AW3110 expressing arsB RP, acr3 RP or arsB EC displayed a higher As resistance compared to the control. The fluorescence intensity was in a linear correlation in the range of 0–2.0 μmol/L of As(III). The intracellular As(III) concentration was negatively related to As efflux activity of As efflux transporter, which was consistent with the As resistance assays. Moreover, arsM derived from R. palustris CGA009 was subsequently introduced to construct an E. coli AW3110 co-expressing arsB / acr3 and arsM, which exhibited higher As(III) resistance, lower fluorescence intensity and intracellular As concentration compared to the engineered E. coli AW3110 expressing only arsB / acr3. The As volatilization efficiency was negatively related to As efflux activity of efflux transporters, the recombinants without arsB / acr3 displayed the highest rate of As volatilization. This study provided new insights into parameters affecting As volatilization with As efflux being the main limiting factor for As methylation and subsequent volatilization in many microorganisms. Graphical abstract: Image 1 Highlights: A novel As biosensor for intracellular As content measurement was developed. The different As efflux transporters exhibited a significant difference in As efflux activity. As efflux transporters were closely related to limited As volatilization and As methylation rate.